Bioethics : legal and clinical case studies - DeMarco, Joseph P. (Broadview Press, 2017)
"Bioethics: Legal and Clinical Case Studies is a case-based introduction to ethical issues in health care. Through seventy-eight compelling scenarios, the authors demonstrate the practical importance of ethics, showing how the concerns at issue bear on the lives of patients, health care providers, and others. A range of central topics are covered, including informed consent, medical futility, reproductive ethics, privacy, cultural competence, and clinical trials. Each chapter includes a selection of important legal cases as well as clinical case studies for critical analysis. The case studies are often presented as moral dilemmas, and are conducive to rich discussion. A companion website offers a curated collection of relevant legal precedents as well as additional case studies and other resources."--